UPAYA MENINGKATKAN KONSENTRASI BELAJAR PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN PANCASILA MELALUI TEKNIK TEAM QUIZ KELAS IV SDN KALIBANTENG KULON 02: penelitian tindakan kelas - Anisa Nuraeini; Jasmine Diva Auranisa; Susilo Tri Widodo; Nur Indah Wahyuni; Nur Khasanah (STKIP Subang, 2023)
Learning concentration is a condition for students' success in achieving changes in their behavior for the better. Learning concentration is also the achievement of educational goals that students can achieve in the learning process activities. For example, the subject of Citizenship Education or what is now known as Pancasila Education has the aim of broadening students' thinking so that they are able to think critically, rationally and responsibly, participate and act intelligently in activities in society, and can develop positively and democratically. This research was motivated by problems encountered in learning in class IV at SDN Kalibanteng Kulon 02. This research is a form of classroom action research (PTK) using observation, interview and documentation data collection techniques. The aim of the research is to increase students' learning concentration through the application of the team quiz technique with research subjects as many as 26 students. The research results show that students' learning concentration increases through the application of the team quiz technique.